Overview of Nutritional Status and Physical Activity in Elementary School Students - Simangunsong, David MT (Jurnal EduHealth, 2022)
Currently, the problem of nutritional status, especially overweight and obesity, is a global health problem that is often faced in various countries. Overweight nutritional status is a state of excess nutrition where the Ministry of Health criteria has a BMI of 25.1-27.0 and obesity nutritional status is a state of excess nutrition where the Ministry of Health criteria has a BMI > 27.0. Problems with nutritional status do not only occur in adults, but also affect children. The nutritional status of overweight and obesity is influenced by physical activity factors carried out by elementary school students in grades 3 to 6 at Sultan Agung Private Elementary School and Methodist Pematangsiantar Elementary School. To study the nutritional status and physical activity of elementary school students in grades 3 to 6 who are overweight and obese at Sultan Agung Private Elementary School and Methodist Pematangsiantar Elementary School in 2019. This research is a descriptive study with a cross-sectional study design. The sampling technique used is Probability Sampling, in this case Total Sampling is used. There were 57.7% and 42.3% students who were overweight and obese at SD Sultan Agung while SD Methodis had 71.4% and 28.6% who were overweight and obese. Frequency of naps per week, 1-3x/week for 65 students (20.8%). Frequency of naps per day, <1 hour/day for 49 students (15.2%). Frequency of watching TV per week, 1-3x/week as many as 98 students (30.4%). Frequency of watching TV per day, 1-2 hours/day as many as 114 students (35.4%). Frequency of exercising per week, 1-3x/week as many as 209 students (65%). Frequency of exercising per day, 1-2 hours/day as many as 160 students (50%). Frequency of playing per week, playing every day as many as 76 students (23.6%). Frequency of playing per day, 1-2 hours/day as many as 74 students (22.9%). Doing household chores per week, 1-3x/week as many as 152 students (47.2%). Using transportation to go to school as many as 258 students (80.1%). Using transportation to travel as many as 285 students (88.5%). Students' physical activity was found to be lacking.